Constitutional Heads and Political Crises - Low, D. A. author. aut Link
VIII, 244 p.
Keywords: A selection of essays about the constitutional crises throughout the Commonwealth since the Second World War, from Australia, Ceylon, Pakistan, Nigeria, Fiji, India, Grenada, Malaysia and Canada, which examines, in particular, the role and involvement of the Governor-General.